The Effect of The Power of Two Type of Active Learning Strategy on The Students’ Learning Outcomes of Indonesian Language Class - Arda Talia; Andi Adam; Abd. Rajab (CV. Eureka Murakabi Abadi, 2023)
The main problem in this study is how to influence the active learning strategy of the Power of Two type on the learning outcomes of Indonesian language students in grade III SD Negeri 3 Batu, Sidrap Regency. This study aims to determine the effect of the active learning strategy of the Power of Two type on the learning outcomes of Indonesian language students. This research is an experimental research using pre-experimental designs with the type of one-goup pretest-posttest design which only has one group of subjects which is carried out without any comparison group and is given treatment using an active learning strategy type The Power of Two. The data analysis technique used the t-test to test the effect of using the Active Learning Strategy Type The Power of Two on students' Indonesian learning outcomes. The results of the research using inferential statistical analysis using the t test formula, it is known that the calculated t value obtained is 13.64 with a frequency of dk = 20–1 = 19, at a significance level of 0.05 obtained t table = 2.093. So, t-count> t-table. It can be concluded that the application of The Power of Two method has an influence on the learning outcomes of Indonesian in class III SD Negeri 3 Batu, Sidrap Regency.